A Case Study of Hypnosis for Phagophobia: It's No Choking Matter. Issue 4 (12th April 2016) - Reid, David B.
Abstract : In this case study the author reviews the benefits of hypnosis for a 13-year-old female suffering from a specific phobia involving a fear of choking and generalized fear of swallowing that resulted in an episode of Restrictive Food Intake Disorder with associated significant weight loss. At the time of the initial consultation, three weeks after her choking episode, the patient weighed 93 pounds. Standing at 5'2", her Body Mass Index (BMI) was 17 (15th percentile) indicative of healthy weight for a child her age and height. She continued to lose weight over the course of 2 months and at her worst weighed 85 pounds (BMI = 15.5, 3rd percentile, classified as underweight). Prior to the incident, she weighed 105 pounds with a BMI of 19.2 (46th percentile). Treatment initially consisted of 12 hypnosis sessions (over a 5-month period), conducted on a weekly and eventually biweekly basis. A scheduled one-month follow-up visit was conducted following the 12th session, at which time the patient was consuming solid foods without fear of choking. Her BMI at that time was 18.7 (39th percentile). Two months after terminating treatment, the patient experienced a mild relapse triggered by conflicts with some female peers. After four additional hypnosis sessions, the patient's symptoms again remitted. During her last session we shared a pizza, providing clear and convincing evidence that she had overcome her fear of swallowing. She retained therapeutic benefits for at least 3 years following treatment.